PENGALAMAN BERINOVASI GURU SMA DALAM PENGAJARAN BAHASA INDONESIA:Studi Deskriptif Kualitatif tentang Implementasi Inovasi Pragmatik pada SMA di Kota Manado dan Bitung serta Kabupaten Minahasa - Senduk, Agus Gerrad (2005)
The study tries to explore the Indonesian language teachers' understanding and mastery of the innovation of pragmatics in the Senior High School Curriculum, and its teaching application within the teaching and learning process of Indonesian language in the classroom. Besides, the study investigates how the teachers' behavior, readiness and commitment in accepting and implementing the pragmatics as one of the innovations in Indonesian language teaching. The study was carried out in Manado, Bitung and Minahasa regencies in the province of North Sulawesi, taking the Senior High Schools as the object or data sources of study. The study was carried out through three phases: orientation, exploration, and member check. Data collection was done through interview, observation, and documentation study. Data analysis was continuously done during the conduction of research. Theories used are those of various innovative approaches in Indonesian language teaching (structural, pragmatic, communicative, and contextual). Theories on pragmatics cannot be separated from other approaches used in Indonesian language teaching so far. The results of study show that there was a low consciousness, less behavior and ability to think critically, reflectively, and anticipatively, no new effort and hard working among the teachers in terms of their acceptance of pragmatic innovation. The value and essence of pragmatic innovation have not become the teachers' intrinsic owning as a result of the instructive, formalistic, centralistic, uniformistic, and birocratic acceptance of an innovation. The pragmatic innovation was accepted not as a totality, as something incomplete or not final and was introduced merely as an "answer". Indonesian language teachers still under-graded the curriculum (basic course outline), as the guidelines which are not strong enough to motivate them in making the students learn communicatively. The clarification of what and how pragmatics is and its characteristics must be mentioned as the curricular elements which are still weak and in-conducive. They really understood the elements of pragmatic teaching system and they applied them according to the principles of pragmatic teaching. The management of pragmatic teaching involving the pedagogical, didactic and methodic values required by the curriculum has not been intensively and professionally achieved and touched. The results show that there are teachers' positive and negative behaviors in implementing the innovation. Various parts directly involved in a new innovation are needed. They should take care of the description of the innovation, development of professional teacher ability, teaching materials and text books, the students, the new procedure or methods of teaching, visual aids or media, standard Indonesian language, and the regional languages.